Development of Physics Blended Discovery Learning Tools (PBDLT) in alignment with The Merdeka Curriculum - Fitria Herliana; Ahmad Farhan; Mutiara Mutiara; Nurulwati Nurulwati; Elisa Elisa; Elmi Mahzum (Universitas PGRI Kanjuruhan Malang, 2025)
Physics learning is inseparable from curriculum updates that always coexist with educational progress. To ensure that students can understand relevant physics concepts/principles/laws and provide them with the skills they need to face problems in the future, it is very important to develop physics learning tools that are aligned with Merdeka's curriculum. The goal of this project is to provide workable Physics Blended Discovery Learning Tools (PBDLT) for the Merdeka curriculum. Research and development using the ADDIE development model—Analysis, Design, Development, Implementation, and Evaluation—is the nature of this kind of study. In this study, PBDLT development was limited to the development stage with research subjects, i.e., 30 students of class VIII-8 of SMPN 2 Banda Aceh in physics subject and 3 science teachers. Expert validation questionnaires (material and learning design specialists) and practicality tests were used to gauge the viability of PBDLT. Following data collection, descriptive quantitative methods with percentage analysis were used to examine the data. The learning design expert validation test yielded 91.5% with a very valid category and a rate of 93.25% for the material expert validation exam. Furthermore, the student response exam yielded 93% with a very good category while the instructor response test yielded 92.7%. The Physics Blended Discovery Learning Tools (PBDLT) developed by the researchers are viable for use in large-scale trials in the learning process within the Merdeka curriculum, according to the research's findings.